2015
DOI: 10.4028/www.scientific.net/ssp.227.75
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Corrosion Properties of High-Mn Austenitic Steels

Abstract: Institute of Materials Science at Silesian University of Technology since 6 years conducts researches to learn about the new dedicated for automotive, railway and military industries. Some of these materials belong to the group of AHS steels, characterized by the twinning induced plasticity (TWIP) effect. It is a new type of steel possessing both a high strength and a great plastic elongation, and an ideal uniform work hardening behaviour. It is therefore a good candidate for deep drawing applications in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…4a). It confirms our earlier results of potentiodynamic tests [14] and supports the data reported by other authors [12][13][14][15][24][25][26]. The values of corrosion potential are similar for thermomechanically treated and cold deformed specimens (Fig.…”
Section: Effect Of Cold Deformation On the Corrosion Resistancesupporting
confidence: 82%
“…4a). It confirms our earlier results of potentiodynamic tests [14] and supports the data reported by other authors [12][13][14][15][24][25][26]. The values of corrosion potential are similar for thermomechanically treated and cold deformed specimens (Fig.…”
Section: Effect Of Cold Deformation On the Corrosion Resistancesupporting
confidence: 82%
“…Corrosion potential value oscillated a −700 mV for all the experimental samples, however, the lowest average Ecorr wa orded for 6Al-4Mn steel (−733 mV) and the highest for 1.5Al-1.5Mn (−680 mV). Nev less, in comparison to earlier high alloyed high strength steel grades with a similar A ratio, the results show a considerable improvement in the corrosion resistance of th terials [9,11,12,[27][28][29][30][31][32]. For instance, Shih et al [28] reported corrosion rates 580 µm and 570 µm•year −1 for Fe-24.4Mn-9.96Al-0.40C and Fe-30.7Mn-13.03Al-0.44C allo spectively, which were subjected to potentiodynamic testing in 3.5% NaCl solutio guably, the improved corrosion resistance of the studied steels can also be attribu relatively low manganese content (1.5 to 4 wt.%), which decreased the significance soluble corrosion products of manganese [10,12,33].…”
Section: Corrosion Testsmentioning
confidence: 52%
“…Austenitic Fe−17Mn−3Al−0.24C, Fe−21Mn−3.5Al−0.29C, and Fe−27Mn−5Al−0.57C steels were studied by Jablonska and Michalik in 3.5 wt.% NaCl solution, and in acid rain solution (molar ratio H 2 SO 4 :HNO 3 :HCl as 1:0.3:0.17) (pH 3.5) [78]. The three steel grades displayed increased corrosion resistance in chloride solution compared to the acid rain solution.…”
Section: Effect Of Al Alloying On High-mn Twip Steel Corrosionmentioning
confidence: 99%